Ardelia Hall: From Museum of Fine Arts to Monuments Woman. Issue 1 (21st March 2014) - Reed, Victoria
Abstract: Ardelia Ripley Hall (1899–1979) served from 1946 until 1962 as the Fine Arts and Monuments Adviser to the U.S. Department of State. In this role she oversaw the recovery and restitution of movable cultural property that had been displaced during the Second World War. In spite of her vast accomplishments, almost nothing has been written on Ardelia Hall, and little is known about her life. She began her career at the Museum of Fine Arts, Boston, but personal circumstances led to her resignation in 1941. During the war, she was employed by the Office of Strategic Services. The expertise she established as an art historian working with the Roberts Commission at this time led to her appointment at the State Department in 1946. This essay traces for the first time Hall's remarkable journey from curatorial researcher to adviser on international art restitution.